Taxonomic review of Aphestia Schiner, 1866 (Diptera: Asilidae: Laphriinae) with description of seven new species - Camargo, Alexssandro; Vieira, Rodrigo; Rafael, José Albertino (Zootaxa, 2024)
A taxonomic review of the Neotropical genus Aphestia Schiner, 1866 was performed and seven new species were described and illustrated: Aphestia amazonica sp. nov., A. dikowi sp. nov., A. fisheri sp. nov., A. fritzi sp. nov., A. nigriseta sp. nov., A. saltuaria sp. nov. and A. spatulata sp. nov. In addition, two species had their status revalidated, Aphestia brasiliensis Schiner, 1866 stat. rev. and A. calceata Schiner, 1867 stat. rev.; together with A. annulipes (Macquart, 1838) and A. nigra Bigot, 1878, increases to 11 the number of known species in the genus. Atomosia affinis Macquart, 1850 stat. rev. et comb. rev. had its status and original combination with Atomosia Macquart, 1838 revalidated. Aphractia andrenoides (Bromley, 1934) stat. rev. et comb. nov. had its status revalidated and a new combination with Aphractia Artigas, Papavero & Serra, 1991 is proposed. Aphestia chalybaea Röder, 1881, is transferred to Cyanonedys Hermann, 1912, becoming Cyanonedys chalybaea (Röder, 1881) comb. nov. with two new synonyms proposed: Cyanonedys leucura Hermann, 1912 syn. nov. and Clariola nigrescens Ricardo, 1912 syn. nov. Descriptions and redescriptions were provided in detail, with characters of male and female terminalia, including detailed illustrations, distribution maps and a key to Aphestia species.